Farmer`s Perception about Resurgence of Brown Planthopper, Nilaparvata Lugens (Stål) in Bangladesh (Bangladesh Rice Journal, 2020)
Studies were conducted on resurgence of brown planthopper (BPH), Nilaparvata lugens (Stål) and its possible management through a survey in six different regions (viz Tanore, Rajshahi; Niamatpur, Naogaon; Nachole, Chapai Nawabganj; Sadar, Dinajpur; Tarash, Sirajganj and Trishal, Mymensingh). Farmer’s perception of BPH resurgence and its management was more or less similar in different regions with some exception. About 60% farmers were able to identify BPH and 40% farmer could identify the pest problem at the later stage of the infestation when burning symptom was visible in patches. All the respondent farmers (100%) relied on use of insecticide where the selection of insecticide as well as its application was not appropriate.Bangladesh Rice j. 2019, 23(1): 21-33